2012
DOI: 10.4236/jmmce.2012.115033
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Phosphate Mixing on Structural, Spectroscopic, Mechanical and Optical Properties of Zinc tris Thiourea Sulphate (ZTS) Single Crystals

Abstract: Zinc tris Thiourea Sulphate (ZTS) is a semi organic non

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Some procedures have been used in many previous works to modify and enhance the properties of ZTS crystal such as heating [12], mixing [17,[23][24][25], and doping [18,22,[26][27][28][29][30][31][32][33][34]. Previous, in terms of heating, it was found that increasing temperature leads to changing the optical parameters of ZTS crystal [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some procedures have been used in many previous works to modify and enhance the properties of ZTS crystal such as heating [12], mixing [17,[23][24][25], and doping [18,22,[26][27][28][29][30][31][32][33][34]. Previous, in terms of heating, it was found that increasing temperature leads to changing the optical parameters of ZTS crystal [12].…”
Section: Introductionmentioning
confidence: 99%
“…One from these studies reported that the phosphate mixed ZTS crystal may be a better NLO material for SHG [17]. Another study demonstrated that 10 mol% of phosphate mixed ZTS crystal has better SHG efficiency than pure ZTS [23]. In addition, magnesium sulfate [24] and urea [25] mixed ZTS crystals have been studied and compared with pure ZTS crystal.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, organometalic non linear optical (NLO) materials have attained immense appeal form researchers due to a range of their technological applications in photonic field [1]. Zinc tris (thiourea) sulfate is one of the most important organometalic non linear optical crystals having applications in laser experiments and for second harmonic generation (SHG).…”
Section: Introductionmentioning
confidence: 99%